2018
DOI: 10.1016/j.compositesa.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Two-matrix composites: Carbon fiber micropultrusions embedded in flexible epoxy matrices

Abstract: Two-matrix composites combine fibers with two distinct matrices. This is achieved by impregnating fiber bundles with a high-stiffness matrix and embedding the cured bundles in a flexible matrix. Two-matrix composites have been shown to offer unprecedented combinations of transverse flexibility and longitudinal tensile strength, and could offer improved fiber alignment and manufacturability. Here, we explore this concept further by embedding carbon fiber micropultrusions in flexibilized epoxy matrices and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In addition, the appliance compatible with magnetic resonance (MR) was pultruded and tested in various MR-guided cases aimed to study the behavior of arteries [ 385 ]. Recently, an experimental study [ 386 ] demonstrated the feasibility of thermoset micropultrusion of 280 µm-diameter carbon fiber elements, and proposed the use of thermoplastic matrices as a recommendation for further research.…”
Section: Applicationmentioning
confidence: 99%
“…In addition, the appliance compatible with magnetic resonance (MR) was pultruded and tested in various MR-guided cases aimed to study the behavior of arteries [ 385 ]. Recently, an experimental study [ 386 ] demonstrated the feasibility of thermoset micropultrusion of 280 µm-diameter carbon fiber elements, and proposed the use of thermoplastic matrices as a recommendation for further research.…”
Section: Applicationmentioning
confidence: 99%
“…171 With the current level of technology, the profiles as small as 280 micrometers in diameter can be pultruded. 172 It is possible to pultrude both thermoset and thermoplastic components. 172,173 An extensive outlook regarding the possible future of thermoplastic micro-pultrusion can be found in the recent paper of Callens and Bergsma.…”
Section: Pultrusion Applicationsmentioning
confidence: 99%
“…172 Generally speaking, knowledge of micro-pultrusion is very limited, and the only applications discussed in the literature so far are the following: medical 174176 and aircraft industry. 172…”
Section: Pultrusion Applicationsmentioning
confidence: 99%
See 2 more Smart Citations